MANAGEMENT OF MONTESSORI-BASED ALTERNATIVE SCHOOLS IN THAILAND: THE HOPE FOR COMPREHENSIVE QUALITY EDDUCATION MANAGEMENT - Napatthirachanchai, Chayanun; Surasakhon, Wirot; Witoonchat, Mantariga; Pengnoo, Thidaporn (Journal of MCU Nakhondhat, 2023)
The alternative school based on Montessori principle is a school that combines philosophy, teaching methods, and learning management with school curriculum. The alternative education based on Montessori principle was invented by Italian physician Maria Montessori, a holistic child development. The purpose of this article is to present the factors of alternative schools administration based on Montessori principle in Thailand. The authors has experience and done research about Montessori principle. The findings are summarized as follows: The factors of alternative schools administration based on Montessori Principle in Thailand include 6 components are 1) Montessori Mission. The management has the vision, knowledge and characteristics and encourages teachers to receive knowledge and experience training in order to support successful management of Montessori concept. 2) Resource Management Policy and Curriculum The school has prepared a project plan to improve the quality of education management in accordance with the Ministry of Education's policy, encouraging personnel to attend training with the International Montessori Association to build understanding for parents and human administration. Budget management, planning, and curriculum management in all aspects of Montessori. 3) Organizing the learning environment, schools promoting the use of media, activities, classrooms and environment according to Montessori concept. 4) Encouraging and encouraging schools to appropriately provide salary, welfare, and compensation to staff. Commend teachers, raise resources from parents, communities, and encourage teachers and staff. 5) Integration, measurement and evaluation. The school integrates the use of local resources. Encourage planning and joint evaluation of personnel using measurement and evaluation tools that are consistent with the purpose 6. Facilities and facilities are managed by the school. The administrative structure is clearly established, and the student support system is in accordance with the learning management. All of these elements are management so that the school can successfully manage the Montessori concept.